Answer:
x = 0 and y = 3
Step-by-step explanation:
Using elimination method, we can solve for x and y in the simultaneous equation
y = 2x + 3 .................................eqn 1
y = -3x + 3 .................................eqn 2
multiply equation 1 by 3 and equation 2 by 2, then we will have
(y = 2x + 3) × 3
(y = -3x + 3) × 2
3y = 6x + 9 ...............................eqn 3
2y = -6x + 6 ................................eqn 4
Add eqn 3 and 4 together and we will eliminate x and have
5y = 15
Divide both sides by 5, and we will have
y = 3
To solve for x, substitute 3 for y in eqn 1
y = 2x + 3
3 = 2x + 3
collect like terms
3 - 3 = 2x
0 = 2x
Therefore x = 0
Answer:
67°
Step-by-step explanation:
A right angle = 90°
90° - 23° = x° = 67°
Answer:
x = -1
Step-by-step explanation:
3(x+1) = -2(x-1) - 4
3x + 3 = -2x + 2 - 4
3x + 3 = -2x - 2
Add the -2x to both sides
5x + 3 = -2
Subtract the 3 to both sides
5x = -5
Divide both sides by 5
x = -1
Answer:
0.01533036946190
Step-by-step explanation:
10÷652.3
0.01533036946190
The formula for finding the surface area of a cube is A=6y^2 where y is the side length. we know a=96. so we just isolate y.
96/6= 6y^2 / 6
16=y^2
sqrt (16) = sqrt(y^2)
4=y
So y is 4